Explain the behavior change and maintenance in diabetic patients using MTM-HAPA framework - Wu, Yibo; Yu, Zhenjie; Yin, Xiaoqiu; Li, Yimiao; Jiang, Yang; Liu, Gongli; Sun, Xinying (Frontiers in Psychiatry, 2024)
ObjectivesThe aim of the study was to to uncover the factors influencing the initiation and maintenance of health behaviors indiabetes mellitus (DM) patients, utilizing baseline data from a randomized controlled trial to construct a structural equation model based on the Multi-Theory Model (MTM) and Health Action Process Approach (HAPA) scales.MethodsThe study recruited participants with type 2 diabetes, aged between 18 and 75 years, from 45 distinct locations in Beijing, China.Patients [N = 406, n = 232 (57.1%) females, n = 232 (42.9%) males; Mean (SD) age = 56.7(10.9)] completed self-reported questionnaire about constructs from integrated theories concerning health behavior. To test the associations between the variables, structural equation modeling with latent variables was employed. Based on the path coefficients of Structural Equation Modeling(SEM), we verified all the hypotheses.ResultsDisadvantages, Advantages, Self-efficacy for Initiating Behavior, and Changes in Physical Environment are all prove to have an effect on intention, with the effect of Disadvantages being negative. Intention positively influenced Action Planning and Coping Planning, both of which in turn significantly predicted Initiation of Behavior Change. Practice for change, Emotional Transformation, Changes in Social Environment, and Self-efficacy for Sustaining Behavior were all affected by Outcome Expectancies and Risk Perception positively. Meanwhile, Practice for change, Emotional Transformation, Changes in Social Environment and Self-efficacy for Sustaining Behavior- would have a significant predictive effect on Maintenance of Behavioral Change.ConclusionThe empirical evidence from this study robustly validates the majority of its theoretical constructs, affirming that MTM-HAPA possess significant explanatory capability in delineating the factors that underpin both the Maintenance of health-related behaviors and the Initiation of Behavior Changes in individuals suffering from DM.